A monolithic 0.35-μm SiGe Class e power amplifier designed at 1.9 GHz - Dos Santos, Antonio Jose S.; Martins, Everson [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents the design of a monolithic 1.9 GHz, Class E, power amplifier (PA) for wireless application with the main components on chip. A cascode topology is used to attenuate transistor stress and to increase the output power, although it compromises the efficiency due to the dissipative process caused by transistor parasitic capacitances. The proposed PA was developed in a single-ended topology because most of the existing components designed use this configuration. The PA was developed in a 0.35-μm SiGe BiCMOS technology with 3.3 Volts which delivers 20.9 dBm output power and 25.5% of power added efficiency (PAE). It also presents a bandwidth of 60 MHz which is suitable for GSM application. Some considerations about the layout are also discussed. © 2013 IEEE.
Keywords: Class E; low power; output power; power added efficiency (PAE); Power amplifier (PA); switching mode; transistor stress; wireless